State and Society in Francophone Africa since Independence
XX, 280 p.
Keywords: This book presents a series of essays by leading English and French scholas examining the politics, economics, international relations and defects of the literary scene of France and the former territories of francophone West Africa since 1965. The approach is emphatically a thematic one rather than a country-by-country analysis.